Technology of modular control advanced learning in the independent work of students - Korniіenko L.; Korniіenko O. (Problems of Engineer-Pedagogical Education, 2023)
The technology of modular control advanced learning as a system of organizational and methodological measures for combining and introducing students into independent work under the guidance of a teacher of advanced learning and tasks for modular control is proposed. The technology is aimed at strengthening the role of independent work in the training of highly qualified specialists. Modular test assignments are developed by the teacher and have certain features. They contain tasks on individual topics of the module, which reflect the main theoretical provisions and practical orientation of the module, and methodological recommendations for studying the module and performing thematic control tasks. Modular test assignments are posted on web resources along with other didactic materials for the academic discipline. Thematic control tasks are individual. They consist of tasks, the solution of which requires the combined use of knowledge and which, in terms of content, are focused on the professional activities of future specialists. It is proposed to perform thematic tasks in a proactive way, that is, before the presentation of the theoretical material necessary for solving the problems. The teacher organizes online consultations to explain the new theoretical positions that are not clear to the student and to direct their thoughts to the construction of an algorithm for solving problems, as well as for the hidden education of students in the process of interactive communication. If the student is not able to complete the task in a proactive way, it is envisaged to perform it in the traditional way after conducting classroom lessons on the subject of the task. Completed thematic assignments are sent to the teacher for an operational review, in which the shortcomings are analyzed with a proposal to repeat the assignment within the stipulated time frame with its additional strengthening. To motivate students to perform thematic control tasks in a proactive way, it is proposed to take into account the factor of independent acquisition of knowledge and their practical application when assessing the assignment. The results of pedagogical experiments in two educational institutions with higher and vocational higher education are presented and analyzed. It is proved that the pedagogical technology of modular-control advanced learning contributes to the formation of the experience of self-education, creative skills and the practical use of knowledge.